Step ordering induced by nonplanar patterning of GaAs surfaces - Volta,AD; Vvedensky,DD; Gogneau,N; Pelucchi,E; Rudra,A; Dwir,B; Kapon,E; Ratsch,C (Applied Physics Letters, 2006)
We report the observation and theory of the morphological evolution of vicinal (001) ridges on V-grooved GaAs surfaces during metal organic vapor-phase epitaxy. The pattern of the nonplanar substrate induces unusual ordering of monatomic steps, different from the free step flow observed on a nonpatterned vicinal surface. The step edges develop profiles that kinetic Monte Carlo simulations reveal are determined by the width of the ridges between neighboring V grooves and the kinetics of interfacet mass migration between the ridge and the bounding sidewalls of the V groove.